Gold‐Catalyzed Enantioselective Synthesis, Crystal Structure, and Photophysical/Chiroptical Properties of Aza[10]helicenes. Issue 28 (3rd June 2016) - Tanaka, Maya; Shibata, Yu; Nakamura, Kyosuke; Teraoka, Kota; Uekusa, Hidehiro; Nakazono, Kazuko; Takata, Toshikazu; Tanaka, Ken
Abstract: The enantioselective synthesis of an aza[10]helicene, possessing two pyridone units, has been achieved by the gold‐catalyzed intramolecular quadruple hydroarylation of a tetrayne. This aza[10]helicene was successfully converted into a fully aromatic aza[10]helicene, possessing two pyridine units. Structure–photophysical and chiroptical properties relationship in a series of azahelicene isomers has also been disclosed. Abstract : The enantioselective synthesis of an aza[10]helicene, possessing two pyridone units, has been achieved by the gold‐catalyzed intramolecular quadruple hydroarylation of a tetrayne. This aza[10]helicene was successfully converted into a fully aromatic aza[10]helicene, possessing two pyridine units. Structure–photophysical and chiroptical properties relationship in a series of azahelicene isomers has also been disclosed (see scheme).